On derivation of equations of dynamics for a certain class of models of mechanical systems - Grabysz, Witold (Computer Assisted Methods in Engineering and Science; Vol 3 No 4 (1996), 2023)
Mechanical systems are quite often modelled as sets of stiff and flexible elements. If some conditions concerning connections of these elements are fulfilled, then we get a physical model having an interesting feature: it is quite easy to derive equations of motion from a diagram representing in a natural, intuitive manner the structure of the system. The algorithm for such derivation, including creation of a simple graphical user interface is presented in the paper. The algorithm takes advantage of the software package MATLAB /SIMULINK.